Design, Synthesis, Molecular Docking, and in vitro Anti-Inflammatory Evaluation of Novel Benzimidazole Derivatives as Potential COX-2 Inhibitors - Bora, Neha Shyam; Bhosale, Mayur Shivaji; Balsane, Amol Sambhaji; Dhamak, Vikrant Murlidhar; Bhor, Rohit Jaysing; Dattatraya, Sagar Magar; KeshavTambe, Sanket (International Journal of Pharmaceutical Investigation, 2026)
Background Cyclooxygenase-2 (COX-2) is a key enzyme involved in inflammation, making it an important target for anti-inflammatory drug discovery. Derivatives of benzoimidazole are well recognized for diverse pharmacological activities, including COX inhibition. Materials and Methods Novel benzimidazole derivatives (NB1-NB6) were synthesized and structurally confirmed through spectral characterization. The COX-2 enzyme (PDB: 4COX) was created with Discovery StudioVisualizer, and Glide was used for docking (Schrödinger suite). Binding interactions were analyzed in 2D and 3D, and results were validated against Celecoxib's crystal structure. In vitro anti-inflammatory activity was evaluated using the protein denaturation method, with diclofenac sodium as the reference drug. Results Docking studies revealed that all compounds exhibited favorable binding affinities (-6.902 to -8.94 kcal/mol). NB6 showed the strongest binding (-8.94 kcal/mol), interacting with key residues ARG120, TYR355, TYR385, TRP387, GLY526, and ALA527. In vitro assays demonstrated concentration-dependent inhibition of protein denaturation, with NB6 and NB4 showing activity comparable to diclofenac sodium. Conclusion The study identified NB6 as the most promising COX-2 inhibitor candidate. According to these results, benzimidazole derivatives possess strong potential for development as selective anti-inflammatory agents.
Keywords: Benzimidazole Derivatives; COX-2 Inhibition; Molecular Docking; Anti-Inflammatory Activity.